2022
DOI: 10.3390/jpm12050790
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Genetic Risk Factors for Drug-Induced Liver Injury Associated with Anti-Tuberculosis Treatment—A Study from Patients of Portuguese Health Centers

Abstract: Drug-induced liver injury (DILI) is an unpredictable and feared side effect of antituberculosis treatment (AT). The present study aimed to identify clinical and genetic variables associated with susceptibility to AT-associated hepatotoxicity in patients with pulmonary tuberculosis treated with a standard protocol. Of 233 patients enrolled, 90% prospectively, 103 developed liver injury: 37 with mild and 66 with severe phenotype (DILI). All patients with mild hepatitis had a RUCAM score ≥ 4 and all patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Isoniazid, rifampicin, pyrazinamide, and ethambutol cause liver damage, which leads to elevated liver transaminases and affects hepatocyte function ( Cavaco et al, 2022 ). The incidence of liver disease increases each year, and the development of drugs to treat drug-induced liver injury has become a hot topic of research worldwide.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Isoniazid, rifampicin, pyrazinamide, and ethambutol cause liver damage, which leads to elevated liver transaminases and affects hepatocyte function ( Cavaco et al, 2022 ). The incidence of liver disease increases each year, and the development of drugs to treat drug-induced liver injury has become a hot topic of research worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…A crucial first step in patients with suspected DILI receiving hepatotoxic drugs is to stop taking the medicine in question ( Andrade et al, 2019 ). Anti-tuberculosis drug-induced hepatotoxicity (ATDH) is the most common adverse effect of anti-TB treatment, and it makes it difficult for patients to adhere to the entire course of anti-tuberculous chemotherapy (AC) ( Cavaco et al, 2022 ). Drugs available for the treatment of liver injury, such as silymarin, have limited clinical use due to their poor pharmacological effects ( Flora et al, 1998 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DILI is considered the consequence of a combination of variable host or non-host risk factors (55,56), which may act by influencing the gut microbiota composition and metabolites (Table 1). Numerous studies have indicated that the reduced abundance of GM species and genes are the drivers of individual susceptibility to DILI (37,52,(57)(58)(59)(60).…”
Section: Composition and Metabolites Of Gut Microbiota And Drug-induc...mentioning
confidence: 99%
“…In addition to the HLA, genes involved with immune signalling such as PTPN22 and ERAP2 have also been reported to be associated with an increased risk of DILI 7,20 . Finally, genetic variants in genes involved with drug disposition have been reported, but the strength of association and risk of DILI are typically not as high as those reported with HLA alleles 21–23 …”
Section: Introductionmentioning
confidence: 99%